2014
DOI: 10.9745/ghsp-d-14-00021
|View full text |Cite
|
Sign up to set email alerts
|

Are pregnant women prioritized for bed nets? An assessment using survey data from 10 African countries

Abstract: Women of reproductive age are generally more likely to sleep under an insecticide-treated net (ITN) than other household members. Universal coverage increases ITN use by all family members, including pregnant women. However, BCC efforts are needed to achieve desired levels of bed net use, which is especially important for pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
7
13
1
1
Order By: Relevance
“…LLIN usage was disproportionately low for children 6–12 years old despite living in households that reported hanging a LLIN the previous night. Consistent with other studies in sub-Saharan Africa, this particular age group may be less prioritized for net usage, particularly when there are not enough nets to cover all members of the household [ 20 , 48 50 ]. Though in such cases, children may still receive some residual benefit from reduced vector abundance in households with LLINs hanging [ 2 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 83%
“…LLIN usage was disproportionately low for children 6–12 years old despite living in households that reported hanging a LLIN the previous night. Consistent with other studies in sub-Saharan Africa, this particular age group may be less prioritized for net usage, particularly when there are not enough nets to cover all members of the household [ 20 , 48 50 ]. Though in such cases, children may still receive some residual benefit from reduced vector abundance in households with LLINs hanging [ 2 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 83%
“…These results were corroborated by a comparative study by Ricotta et al [39] and 2011 found a similar uniform situation over time-even after mass distribution of LLINs [23]. Similar results were found in a study in Indonesia, Timor-Leste [41].…”
Section: Decision-making Process For Llin Recipientssupporting
confidence: 84%
“…ITN ownership has been a common factor for not using ITNs in other studies [14, 15], though ownership in itself does not guarantee the use of ITNs [21]. In this study conducted in 2010, most of the respondents (57.2%) had received free ITNs or had purchased ITNs at subsidized rates from a public health facility.…”
Section: Discussionmentioning
confidence: 76%
“…However, access does not always result in usage due to sociocultural and logistical reasons [15]. Evidence from some parts of Ghana has shown that over 40% of ITNs available in the households go unused [16].…”
Section: Introductionmentioning
confidence: 99%